The Effect of Profitability (ROA) And Liquidity (CR) on Firm Value (PBV): Study at One of The Selected Airlines on the IDX - Heny Septia Wulandari; Nita Yura Roslina (Majalah Bisnis & IPTEK, 2023)
This study aims to assess the impact of Profitability and Liquidity on the valuation of PT Indonesia Air Asia Tbk from 2017 to 2021. The present study falls under the category of quantitative research. The population under study comprises the financial statements of PT Indonesia Air Asia Tbk. The sample utilized in this study is derived from PT Indonesia Air Asia Tbk's quarterly financial report, employing a time series design sampling technique. The data collection techniques employed in this study involve using financial reports available on the official website of the Indonesia Stock Exchange, specifically www.idx.co.id. The employed analytical methodology is multiple linear analysis. The findings indicate no significant positive relationship between Profitability and Firm Value, as evidenced by a t-count value of 0.142 and a significance value of 0.889, more significant than the threshold of 0.05. However, Liquidity has a significant positive impact on Firm Value, as indicated by a t-count of 3.446 and a significance value of 0.003, which is less than the threshold of 0.05. Furthermore, when both Profitability and Liquidity are considered together, they significantly positively influence Firm Value, with a significance value of 0.003 and an R square of 49.6%. The research findings propose that corporations consider the comprehensive market and industry conditions when developing their business strategies. Ongoing assessment of the organization's fiscal performance is imperative in order to discern prospective enhancements and address potential challenges that may manifest in the future. By comprehending the impact of Return on Assets (ROA) and Capital Ratio (CR) on Price-to-Book Value (PBV), organizations can formulate more suitable business strategies and prioritize the attainment of sustainable growth and enhancement of corporate value.